Propensity Score–Matched Analysis Comparing Minimally Invasive Ivor Lewis Versus Minimally Invasive Mckeown Esophagectomy. Issue 1 (January 2020) - van Workum, Frans; Slaman, Annelijn E.; van Berge Henegouwen, Mark I.; Gisbertz, Suzanne S.; Kouwenhoven, Ewout A.; van Det, Marc J.; van den Wildenberg, Frits J. H.; Polat, Fatih; Luyer, Misha D. P.; Nieuwenhuijzen, Grard A. P.; Rosman, Camiel
Abstract : Introduction: Totally minimally invasive esophagectomy (TMIE) is increasingly used in treatment of patients with esophageal carcinoma. However, it is currently unknown if McKeown TMIE or Ivor Lewis TMIE should be preferred for patients in whom both procedures are oncologically feasible. Methods: The study was performed in 4 high-volume Dutch esophageal cancer centers between November 2009 and April 2017. Prospectively collected data from consecutive patients with esophageal cancer localized in the distal esophagus or gastroesophageal junction undergoing McKeown TMIE or Ivor Lewis TMIE were included. Patients were propensity score matched for age, body mass index, sex, American Society of Anesthesiologists classification, Charlson Comorbidity Index, tumor type, tumor location, clinical stage, neoadjuvant treatment, and the hospital of surgery. The primary outcome parameter was anastomotic leakage requiring reintervention or reoperation. Secondary outcome parameters were operation characteristics, pathology results, complications, reinterventions, reoperations, length of stay, and mortality. Results: Of all 787 included patients, 420 remained after matching. The incidence of anastomotic leakage requiring reintervention or reoperation was 23.3% after McKeown TMIE versus 12.4% after Ivor Lewis TMIE ( P = 0.003). Ivor Lewis TMIE was significantly associated with a lower incidence of pulmonary complications (46.7% vs 31.9%), recurrent laryngeal nerve palsy (9.5% vs 0.5%), reoperations (18.6% vs 11.0%), 90-day mortality (7.1% vs 2.9%), shorter median intensive care unit length of stay (2 days vs 1 day) and shorter median hospital length of stay (12 vs 11 days) (all P < 0.05). R0 resection rate was similar between the groups. The median number of examined lymph nodes was 21 after McKeown TMIE and 25 after Ivor Lewis TMIE ( P < 0.001). Conclusions: Ivor Lewis TMIE is associated with a lower incidence of anastomotic leakage, 90-day mortality and other postoperative morbidity compared to McKeown TMIE in patients in whom both procedures are oncologically feasible.